Transcriptome analysis of the aged SAMP8 mouse model of Alzheimer’s disease reveals novel molecular targets of formononetin protection - Liu, Bo; Cui, Di; Liu, Jie; Shi, Jing-Shan (Frontiers in Pharmacology, 2024)
Background Senescence-accelerated mouse prone 8 (SAMP8) and age-matched SAMR1 mice are used to study the pathogenesis and therapeutics of Alzheimer’s disease (AD); however, the molecular mechanisms are not completely understood. Objective This study aimed to examine the effects of the 5-month administration of formononetin in SAMP8 mice and used RNA-seq to explore the molecular targets. Methods SAMP8 mice were orally administered formononetin (0, 8, and 16 mg/kg) from 4 months of age, and age-matched SAMR1 mice were used as controls. Behavioral tests were performed in 9-month-old mice, followed by histopathologic analysis. Total RNA from the hippocampus was isolated and subjected to RNA-seq, RT-qPCR, and bioinformatics analysis. Results The 9-month-old SAMP8 mice exhibited cognition deficits, evidenced by novel object recognition, open-field test, elevated plus maze, and passive avoidance. Nissl bodies in the cortex and hippocampus were decreased. Formononetin treatments ameliorated behavioral deficits and improved morphological changes, which were evidenced by Nissl and H&E staining. RNA-seq revealed distinct gene expression patterns between SAMP8 and SAMR1 mice. Differentially expressed genes in SAMP8 mice were attenuated or normalized by formononetin. Ingenuity pathway analysis (IPA) of canonical pathway and upstream regulators revealed increases in proinflammatory factors and immune dysfunction and decreases in NRF2 and SIRT-1 signaling pathways, leading to neuroinflammation. Formononetin treatment attenuated or reversed these molecular changes. The transcriptome of SAMP8 mice was correlated with transcriptomic profiles of other AD mouse models in the GEO database. Conclusion Neuroinflammation and decreased antioxidant and SIRT-1 signaling contributed to cognitive deficits in aged SAMP8 mice, which are potential therapeutic targets of formononetin in combination with other therapies.